Study of nutrient foramina in fibula: its applied importance - Dutta, Malamoni; Mahanta , Putul; Baro, Baneswar; Hazarika , Devid (Journal of Indian Academy of Forensic Medicine, 2020)
The external opening of the nutrient canal is usually referred to as the nutrient foramen. The term ’Nutrient’ itself describes the role of nutrient foramina in the nutrition and overall growth of the bones. The diaphyseal nutrient artery is the primary source of blood to entire osteal tissue and bone marrow of a long bone, especially during its active growth period and the early stages of ossification. Therefore, they play a very significant role in the healing of fractures and prevention of avascular bone necrosis. Every nutrient foramen has a particular position in each bone and fibula is of no exception. However, the number and location of nutrient foramina may very sometimes. In bone graft and vascularised surgery, the fibula is commonly used. Therefore, an understanding of the position and number of nutrient foramina in fibula is essential. Moreover, fibula flap is the most widely accepted flaps used in the mandibular reconstruction surgery, especially in the malignancy of oral and oropharyngeal regions. This review paper outlines the anatomical variation of the nutrient foramen of the fibula and its applied importance in clinical practice.